THE CIS AND GUAM - GROZIN, Andrey (CENTRAL ASIA AND THE CAUCASUS, 2008)
From almost the very beginning of the post-Soviet era, the territory the Soviet Union left behind became an arena of tough rivalry and confrontation among several world centers of power. The United States, Russia, China, the European Union, and the Muslim world can be described as the most active players. The latter is represented by individual countries and official organizations, as well as illegal radical structures. Nearly all of the actors mentioned above (with the exception of China, because of its special position) are more or less interested in trimming Russia’s influence across the post-Soviet expanse, thus strengthening their own position in the region.America is especially active in this respect; to achieve its aims it is using both governmental structures and all sorts of NGOs and nonprofit organizations operating in the post-Soviet states. Washington has already spent a lot of money to entice the ruling circles of several of them to its side.The Commonwealth of Independent States is obviously losing its importance as an interstate integration structure. Today, we can even say that it is falling apart into individual structures, each with foreign policy orientations of its own. The first signs of this were apparent at the very early stage: Ukraine, for example, refused to sign the CIS Charter.Belarus, Armenia, Kazakhstan, Tajikistan, Kyrgyzstan, and Uzbekistan remain Russia-oriented, partly because of their membership in several regional structures of economic or military-political orientation: the Collective Security Treaty Organization (CSTO) and the Eurasian Economic Community (EurAsEC). On the other hand, several countries pooled their efforts to squeeze Russia at least out of the most important spheres of interstate relations. Supported by the United States, they set up a regional organization of their own called GUAM (Georgia, Ukraine, Azerbaijan, and Moldova) as a counterweight to the pro-Russian structures. In the last few years, the pro-Russian political forces in these countries have lost much of their former influence, not only in the foreign policy sphere, but also on the domestic scene. The Georgian leaders, for example, make no secret of their anti-Russian position, which gives Moscow reason to look at them as American puppets. Despite the fact that GUAM was set up back in 1997, its international status is fairly recent: it dates to 2006 when the members gathered together in Kiev for their first summit.1 It acquired a new name—the Organization for Democracy and Economic Development—GUAM, a Charter, and headquarters in Kiev It should be said that all analyses of GUAM, the CIS, EurAsEC, and CSTO are based on analysts’ political biases. If an analyst believes that American and EU influence in the post-Soviet expanse is obviously beneficial, he will spare no compliments when talking about the “post-Soviet democracies.” More likely than not, such people tend to ignore the undemocratic developments in these countries. Typically enough, Deputy Foreign Minister of Russia Grigory Karasin offered the following comment on the eve of the Vilnius GUAM summit, which marked the Organization’s first decade: “So far it is hard to offer positive comments about an organization that has been working for ten years now. Time will show. It is much more interesting to discuss another aspect: the correlation between the United States (itself not a member) and the GUAM countries.”2 President of Kazakhstan Nursultan Nazarbaev was even more straightforward. In his interview to El Pais he said: “GUAM is a purely political structure and I don’t believe that its horizons are vast.